Pendidikan Karakter Peserta Didik Program Kampus Mengajar di Sekolah Dasar - Nihlatun Niswah; Erna Zumrotun; Syailin Nichla Choirin Attalina (Universitas Negeri Padang, 2023)
The multidimensional crisis that has been rife recently has become a complex problem that has impacted the decline in the character of society, especially among students. Seeing this urgency, the government continues striving to improve Indonesian education quality through the independent learning policy. In general, the focus of the teaching campus program is in the form of assisting the implementation of learning in schools which includes increasing students' literacy and numeracy, assisting school administration management, and introducing technology adaptations for educators and students. This research aims to determine how character education is implemented in the 4th batch Teaching Campus program at SDN 1 Bringin. The research method used is a qualitative type of field research (field research) through a case study approach. The data collection technique used is data triangulation, including; interview, observation, and documentation. The results showed that the implementation of character education in the Teaching Campus program batch 4 at SDN 1 Bringin was based on the six pillars of the Pancasila student profile. The form of program implemented is in the form of 5S habituation, the habituation of asmaul husna, the habit of singing national and regional songs, cooperation in cleaning the environment, the habit of being independent, critical thinking, making wall magazines, as well as interesting and varied learning. Based on the program that has been implemented, it can be seen that there has been an increase in the character values ​​of students, as evidenced by increasing religious values, cooperation, courtesy, creativity, independence, and students' thinking skills in learning.